Abrupt Climate and Weather Changes Across Time Scales. Issue 9 (11th September 2020) - Lohmann, Gerrit; Butzin, Martin; Eissner, Nina; Shi, Xiaoxu; Stepanek, Christian
Abstract: The past provides evidence of abrupt climate shifts and changes in the frequency of climate and weather extremes. We explore the nonlinear response to orbital forcing and then consider climate millennial variability down to daily weather events. Orbital changes are translated into regional responses in temperature, where the precessional response is related to nonlinearities and seasonal biases in the system. We question regularities found in climate events by analyzing the distribution of interevent waiting times. Periodicities of about 900 and 1, 150 yr are found in ice cores besides the prominent 1, 500 yr cycle. However, the variability remains indistinguishable from a random process, suggesting that centennial‐to‐millennial variability is stochastic in nature. New numerical techniques are developed allowing for a high resolution in the dynamically relevant regions like coasts, major upwelling regions, and high latitudes. Using this model, we find a strong sensitivity of the Atlantic meridional overturning circulation depending on where the deglacial meltwater is injected into. Meltwater into the Mississippi and near Labrador hardly affect the large‐scale ocean circulation, whereas subpolar hosing mimicking icebergs yields a quasi shutdown. The same multiscale approach is applied to radiocarbon simulations enabling a dynamical interpretation of marine sediment cores. Finally, abrupt climate events also have counterparts in the recent climate records, revealing a close link between climate variability, the statistics of North Atlantic weather patterns, and extreme events. Plain Language Summary: Predicting the future spread of possible climates, the risk of climate extremes and the risk of rapid transitions is of high socioeconomic relevance. The past provides evidence of abrupt climate change and the frequency of extremes. This allows to separate anthropogenic signals from natural climate variability. Earth system models applied both to past and future scenarios will enhance our ability to detect regime shifts which are necessary to potentially predict climate extremes and transitions. We consider the response of the system to regular orbital forcing and then focus on shorter time scales down to weather. The appearance of precession is linked to nonlinear responses of the climate system to external orbital forcing. Furthermore, we find that centennial‐to‐millennial variability is stochastic in nature. We also discuss recent developments of climate models with superior resolution in typical retrieval regions of paleoclimate records, such as continental margins and coasts. Using this model, we find a strong sensitivity of the Atlantic meridional overturning circulation depending on where the deglacial meltwater is injected into. Meltwater into the Mississippi and near Labrador hardly affect the large‐scale ocean circulation, whereas subpolar hosing related to icebergs yields a quasi shutdown. Our multiscale approach is applied to radiocarbon simulations enabling a dynamical interpretation of marine sediment cores. Finally, we explore a close link between climate variability, the statistics of weather patterns, and extreme events. Key Points: Nonlinear response of the climate system to external orbital forcing yields responses in the precessional band Centennial and millennial variability are stochastic in nature Ocean and radiocarbon modeling with high resolution at the coasts and high latitudes provides a suitable framework for multi‐scale dynamics The past provides evidences of abrupt climate changes and weather extremes